MEDICAL-SURGICAL NURSING CARE MANAGEMENT WITH A SERVICE EXCELLENCE APPROACH FOR MR. H WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) AT RSUP H. ADAM MALIK, MEDAN CITY, NORTH SUMATRA, IN 2025 - Desi Imelda Manalu; Sri Murtini; Siagian, Ramelina Y W; Masda Yanti Lase; Marcus Vinensius Hia; Delima Manik; Naila Kamila, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by airflow limitation due to chronic inflammatory responses to inhaled particles or gases. COPD ranks among the leading causes of death worldwide and has a high prevalence, including in North Sumatra Province. This study aims to describe the management of medical-surgical nursing care based on service excellence principles for a COPD patient, specifically Mr. H, who was treated in Room RA6 of RSUP H. Adam Malik Medan. The research method employed is descriptive, using a case study approach. Nursing care was carried out systematically through the stages of assessment, nursing diagnosis, planning, implementation, and evaluation. Interventions focused on managing ineffective breathing patterns, airway clearance, activity intolerance, and anxiety, with the application of service excellence values, including empathy, effective communication, and patient and family education. The results showed that comprehensive and collaborative nursing care improved the patient's clinical condition and accelerated recovery. This study recommends enhancing family education and strengthening nurses' competencies in the professional and ethical management of patients with COPD.